Efektivitas Relaxed Sitting Dengan Pursed Lips Breathing Terhadap Penurunan Derajat Sesak Napas Pasien Penyakit Paru Obstruktif Kronik Di RSUD Dr. M. Yunus Bengkulu - Lina, Liza Fitri; Wijaya, Andri Kusuma; Admaja, Rengga Depri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: Chronic Obstuctive Pulmonary Disease (COPD) increases morbidity and mortality by causing various levels of disturbances including coughing, chest pain, congestion, odema, changes in breathing patterns, and changes in posture.Methods: The research design was quantitative research by using a quasy experimental design, two groups pre test and post test design.Results: The results of the bivariate analysis of the dependent t-test in the relaxed sitting treatment group obtained p-value 0.019, while in the treatment group pursed lips breathing the results of p-value is 0.000. The independent t-test results obtained p-value 0.004.Conclusion: The conclusion of this study shows a comparison of the effectiveness of relaxed sitting with pursed lips breathing to decrease the degree of congestion of patients with COPD.